1900
DOI: 10.1007/bf01994661
|View full text |Cite
|
Sign up to set email alerts
|

Ueber Knorpel- und Knochenbildung in Herzklappen

Abstract: KnorpeI-m~d Knoehenbildung sind aueh in solehen Ge~veben, deren eigentliche Textur dem Knorpel oder Knochen ganz fi'emd is~, schon iJfter beobachtet worden; abgeseh@ yon den unter dem Namen des ,,Teratome ~' zusammengefassten Gesehwiilsten, welehe else dutch versprengte embryonale Keimanlage erkl~i.rbare Neubildung darstellen, und bei denen das Vorkommen yon Knorpel oder Knochen im Hoden, der Parotis, der Mamma~ u. s. w. keine fiberraschende Seltenheit mehr ist, giebt kS eine P~eihe von F/illen, in denen Knoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1903
1903
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…One site where fibrous connective tissue can be transformed into fibrocartilage is within the wall of the aorta. This was first described by Andral (1827) and has been mentioned frequently in descriptions of arterial lesions since that time (Howse, 1877;Rosenstein, 1900;Bunting, 1906, etc.). Two further changes have been observed that are typical of cartilage and not of fibrous tissue.…”
mentioning
confidence: 84%
“…One site where fibrous connective tissue can be transformed into fibrocartilage is within the wall of the aorta. This was first described by Andral (1827) and has been mentioned frequently in descriptions of arterial lesions since that time (Howse, 1877;Rosenstein, 1900;Bunting, 1906, etc.). Two further changes have been observed that are typical of cartilage and not of fibrous tissue.…”
mentioning
confidence: 84%
“…Durch die wissenschaftliche Prägung James Israels war Rosensteins wissenschaftliches Oevre nicht rein urologisch ausgerichtet [25,26,27,28], sondern umfasste auch allgemeinchirurgische [29], infektiologische [30] und onkologische [31] und in seiner Frühzeit ebenfalls auch pathologische [32] Themen. Auch war die Fachdifferenzierung der Urologie zu diesem Zeitpunkt keineswegs abgeschlossen.…”
Section: Wissenschaftliches Werkunclassified